Voters’ attitudes towards political parties’ communication: the case of Diepsloot voters in Gauteng, South Africa - Trevor Hlungwani; Siyasanga Tyali (Communicare)
This article investigates how South African political parties’ communication strategies influence voters’ decision-making. The study sought to understand the effects and influences of political communication approaches on voters’ decision-making processes. The election periods used for the analysis are the 1999 to 2019 general elections. The focus area of the study was Diepsloot, a densely populated township in the north of Johannesburg in Gauteng, South Africa. Furthermore, the researchers also assessed whether Diepsloot residents understood political communication, especially during an election period. The research focused on the African National Congress (ANC), the Democratic Alliance (DA) and the Economic Freedom Fighters (EFF). These parties were the top three when it came to electoral support in South Africa when this study was carried out. Data were gathered using open-ended telephonic interviews with voters in Diepsloot. While the study found that political communication affected a voter’s choice, it also revealed that a voter’s attitude towards these political communication interventions was one of caution. The article concludes that political communication is one of many discernible variables influencing voters when voting for a political party.